Characterisation of Portuguese RC Precast Industrial Building Stock. (8th August 2020) - Rodrigues, H.; Sousa, R.; Vitorino, H.; Batalha, N.; Varum, H.; Fernandes, P.
Abstract : The construction of a vulnerability model requires reliable information on the features of the buildings in the study. The purpose of this work is the characterisation of the precast industrial buildings in Portuguese industrial park, based on the survey of 73 design projects of existing buildings. The collected data are based on a previous study on the features that influence the seismic response of this type of buildings. The parameters collected are associated with the global geometry and specific elements characteristics (e.g., column dimensions, reinforcement ratios, and connections details), to the mechanical properties of the materials and other parameters that can give some important information in the characterisation of the buildings (e.g., construction year and localization). In the end, a comparison with other available databases, namely, from Italy and Turkey, is done in order to conclude about the similarity. This information is important to define representative experimental specimens and numerical simulation to conduce seismic risk analysis.